Planning for the management of agricultural residues a case study of selected municipalities (Tigbao and Labangan) in Zamboanga Del Sur Province, Philippines - Wang, Songlin (2007)
This paper presents the results of the study on agricultural residues management (ARM) in two(2) selected Municipalities, Tigbao and Labangan of Zamboanga del SUl (ZDS) Province. The research was basically a case study, which focused on rural areas and the planning for the management of agricultural residues (ARs). The main aim of the study was to identify appropriate ARM strategies to improvement current status of ARM in the 2 municipalities through the following: 1)assessment of the current status of ARM in the 2 municipalities; 2)identification of problems/concerns/issues of ARM; 3)analysis and recommend ARM strategies and the disposal practices at individual households; 4) formulation of action programs on ARM for the 2 municipalities; and 5) presentation of projected benefits to the 2 municipalities if action programs followed and implemented.Data collection was conducted mainly through the survey method, particularly through questionnaires filled out by rural households and government officials, as well as, interviews with some key informants. A review and analysis of documents/reports was also done, and actual observations were made of the ARM conditions in the study areas. Two different sets of questionnaires were administered to the municipal government officials and households. Data obtained were analyzed and summarized by extracting frequencies percentages and regressions. The study is heavily based on primary data gathered from the questionnaire survey and key informant interviews, since no relevant research on the topic had been done before. Firstly, by applying quantitative and qualitative analyses, this study examines the current government policy regarding ARM in the Province of Zamboanga del Sul, particularly the Municipalities of Tigbao and Labangan, and probable strategies to be used to solve the problem of ARs. Secondly, the study also analyzed the current households' disposal practices of their agricultural residues, and the technologies and problems they face. Finally, the study also sought to determine the factors influencing ARM. It is expected that this study can raise more concern from the government about the importance and necessity of proper ARM; more attention from government will be given towards the future consequences and financial implication of ARM and thereby some policies will be formulated to support the farmers to make use of their ARs. Furthermore, it can provide inputs for long-term policy decisions on ARM strategy and for further studies that seek a permanent solution to the ARM. Likewise, the study may contribute to increasing the people's awareness of environmental protection and proper ARM. In addition, the study may provide guidelines for ARM in the rural areas of Zamboanga del Sur and, if proven successful, may be replicated in other rural areas of the country. As in some other developing countries like the Philippines, ARM is relatively a new topic especially in the study areas. ARM is not a priority concern of the LGUs. They have not formulated any explicit policies regarding ARM with clear direction and objectives. Although some awareness campaigns have been conducted to induce and encourage farmers to dispose their agricultural residues properly by using some composting technologies, most of the farmers still practice the traditional method of disposing their agricultural residues which, on the one hand, pollutes the environment, and likewise for most of the agricultural solid waster resources on the other hand, are recyclable and re-useable. The reasons for this are the following: firstly, some farmers lack the information on how to properly dispose their agricultural residues because the awareness campaigns conducted by the government did not reach most of the farmers. Secondly, the farmers were poor and resisted the use of the technology because it would be an additional expense for them. Finally, the lack of effective technology also affected the farmer's expectations. The current strategies used by the two LGUs in their respective ARM programs have not been effective in bringing about significant and long-term improvements in the farmers' disposal practices and in solving the ARM problem. These inadequacies were brought about by the absence of explicit policies and appropriate intervention strategies that address present and future directions. The essential reason here is that the problem of ARM is due to the lack of government concern, in which the ARM is not a priority agenda of key leaders. Furthermore, the ARM programs have not been included in their municipal plan and budget. There is a need for the municipalities (particularly Tigbao and Labangan) to initiate intervention strategies to solve the ARM problem effectively. Recommendations for appropriate ARM strategies to address the ARM problem were identified and the program for action was also provided. The recommended strategies are shown in the following: First of all, formulate a clear and explicit policy with clear direction and objectives, and formulate appropriate ordinances and disposal standards on ARM that are applicable in their areas. Set disposal standards for different categories of ARs which can be used to guide and regulate ARs disposal activities, and for strictly enforcing these ordinances as well. Second, prepare a strategic ARM plan, which should be incorporated into the municipal development plan and include the ARM program in the municipal budget. Third, effective technologies are also important to prevent residues from becoming a waster and to turn them into harmless and useful resources. Fourth, public involvement and support are absolutely necessary to ensure the success of any program and all stakeholders should be involved by raising their awareness through information and education campaign. In addition, cooperation with private investors, enterprises, voluntary organizations an NGOs is absolutely necessary in order to ease the burden of the government, as well as, to solve the ARM problem. Last, but not the least, and in order to encourage farmers to adopt the technology to dispose ARs properly, the government should subsidize farmers in implementing demonstration projects.